IOT-based solution towards real-time monitoring system for high jump spot - Roslan, Muhammad Faris (2019)
In high jump sport, approach speed is one (1) of the important parameters to maintain the speed as well as to gain good momentum at the ankle during the take-off. The good approach speed can prevent injury at the ankle for the athlete. Today, high jump athletes still use high-speed camera to guide them in training by capturing all of the athletes’ movements. This is because, there is no wearable device that can monitor the athlete performance during the training in real-time. Thus, the aim of this study is to develop a wearable Internet of things (IoTs) device that measures the speed during the approach speed and force during the take-off to help athletes to improve the performances and prevent injury at the ankle during take-off. This IoT device has implemented real-time monitoring systems (RtMS) that used IoTs as a connectivity which includes input, process and output. The input consists of global positioning system (GPS) sensor attached to the waist and force sensors placed at the bottom of the ankle as a wireless input for data capturing. These data is then being processed by microcontroller units (MCUs) with an embedded Wi-Fi module on the same chip that has been programmed and the results obtained are displayed on the mobile application (app). Other than that, there is a vibrator motor placed near the GPS sensor which acts as an actuator output that will vibrate according to the speed setting of the athletes. Apart from that, the latency and throughput of the two (2) different MCUs were also measured and compared to investigate the network transmission issues during the sport event. The ESP8266 MCU has been selected as the result shows that it has high throughput, low latency and small in terms of size compared to Arduino Yun Mini MCU. This system shows a significant result when intermediate athletes tested the devices with and without using the alarm system. Hence, it is shown that the implementation of wearable devices that monitored speed and force parameter helps to improve the performance of the athlete by following professional benchmark data.